Treatment of Diabetic Gastroparesis by Complementary and Alternative Medicines - Liu, Hao (Medicines (Basel), 2015)
Gastroparesis is a common gastrointestinal complication in diabetes, induced by hyperglycemia and characterized by delayed gastric emptying and upper abdominal symptoms, such asnausea, vomiting, early satiety, bloating and epigastric pain. Diabetic gastroparesis (DGP) affects life quality and glycemic control, and is a challenge to treat in both Western and Eastern medicine. Routine treatment in Western medicine includes gastric emptying promoted by prokinetic agents, gastric pacemaking, or surgery combined with lifetime hormono-therapy, all of which have unavoidable side effects and limitations, and are very expensive. Complementary and alternative medical treatments like acupuncture, moxibustion, and massage are becoming more and more attractive because of their effectiveness, fewer side effects, and reliable safety. This article aims to introduce representative methods of complementary and alternative medicine to treat DGP, which were searched in English through Pubmed and in Chinese through CNKI (China Knowledge Resource Integrated Database). Several lines of evidence demonstrated the effects of single or combined complementary alternative therapies on DGP outcomes; however, the mechanisms were rarely investigated. Randomized controlled trials are undoubtedly required in future studies.